ANALISIS BIBLIOMETRIK: TREND PENELITIAN PENDIDIKAN POLITIK (1993- 2023) - Abdul Rasyd, Muhamad Rafi; Alfy, Riadh; Utama, Rd. Dian Herdiana; Muhammad, Ilham (Comm-Edu (Community Education Journal), 2024)
This study scrutinizes the evolution of political education research over three decades, aiming to identify the most prolific authors, affiliations, and countries, to map research trends, and to suggest directions for future inquiry. Utilizing bibliometric methods, data were collected from Scopus and WOS databases, converted into RIS format, and analyzed with Rstudio and VosViewer. Findings reveal a marked increase in political education research, highlighting its growing significance in response to current global dynamics. The United States stands out with the highest international citation count, indicating its pivotal role in the field. The analysis underscores the relevance of linking political education to a country's political landscape. Consequently, this research advocates for more nuanced studies on the application of political education tailored to national contexts, to enhance its efficacy and impact globally.